Sigmund Freud and a confusion always implicit in his explanation about God - Mora Calvo, Hernán (2025)
Establishing the meaning and dimensions of the theme of God in Sigmund Freud’s thought is difficult and should not be confused with his views on religion. What does Freudian thought about God consist of and how is it articulated? Is it a vicious circle or a conflict that progresses from definition to definition?